2019
DOI: 10.1155/2019/6063832
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of Magnesium Oxide Nanoparticles as Bactericidal Agents

Abstract: Increased antibiotic resistance of microorganisms as well as the need to reduce health-care costs necessitates the production of new antimicrobials at lower costs. For this reason, this study was aimed to optimize the synthesis of magnesium oxide nanoparticles with the greatest antibacterial activity. In this study, 9 experiments containing different proportions of the factors (magnesium nitrate, NaOH, and stirring time) effective in the synthesis of magnesium oxide nanoparticles were designed using the Taguch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Researches have suggested that magnesium oxide nanoparticles possess excellent antibacterial activity though this mechanism depends on the binding of nanoparticles to the surface of the bacteria [91,92]. They have known to show an increase in antibacterial activity against gram positive bacteria in comparison to gram negative because the latter holds a complex outer membrane which serves as an outstanding barrier against external materials but still magnesium nanoparticles have got hold of gram negative bacteria such as E coli and Staphylococcus aureus and showed antibacterial activity against them preventing cell death of many cells by reducing oxidative stress, lipid peroxidation as well as cell membrane damage [5,32,[93][94][95]. Problems such as foot and mouth disease in cattle's, foodborne pathogens, treatment of the cotton fabric, the quality of bone cement used in fractures, medicine for bone regeneration and abdominal pain comprise of a common solution i.e., magnesium oxide nanoparticles [5,[96][97][98].…”
Section: Therapeutics Based On Magnesium Oxide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches have suggested that magnesium oxide nanoparticles possess excellent antibacterial activity though this mechanism depends on the binding of nanoparticles to the surface of the bacteria [91,92]. They have known to show an increase in antibacterial activity against gram positive bacteria in comparison to gram negative because the latter holds a complex outer membrane which serves as an outstanding barrier against external materials but still magnesium nanoparticles have got hold of gram negative bacteria such as E coli and Staphylococcus aureus and showed antibacterial activity against them preventing cell death of many cells by reducing oxidative stress, lipid peroxidation as well as cell membrane damage [5,32,[93][94][95]. Problems such as foot and mouth disease in cattle's, foodborne pathogens, treatment of the cotton fabric, the quality of bone cement used in fractures, medicine for bone regeneration and abdominal pain comprise of a common solution i.e., magnesium oxide nanoparticles [5,[96][97][98].…”
Section: Therapeutics Based On Magnesium Oxide Nanoparticlesmentioning
confidence: 99%
“…Fortunately, abundant nanoparticles can be used to fulfill the needful among which magnesium oxide nanoparticles remains comprised. Magnesium oxide nanoparticles can be used as an alternative for various traditional antibiotics because of its antibacterial properties [108]. E.R.…”
Section: Therapeutics Based On Magnesium Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the medical advances in recent years, some diseases such as AIDS [8], [9], cancer [10], [11], infectious diseases [12], diabetes [13], chronic pain [14], [15] and autoimmune diseases [16], [17], have not been treated. Since nanoparticles are the foundation of nanotechnology, their use in the medical branch has opened new perspectives in therapy [18].…”
Section: The Nanomaterials and Their Application In Medicinementioning
confidence: 99%
“…One of the main challenges facing the global community today is discovering effective therapies for cancer (Mozaffari et al, 2016;Mozaffari et al, 2017), chronic pains (Sharifi et al, 2017), chronic kidney disease (Nomani et al, 2016), autoimmune diseases (Mozaffari et al, 2018), and microbial infections (Taran et al, 2018;Imani and Safaei, 2019). Microbial infections are historically considered as major pathogenic factors causing mortality around the world (Li and Webster, 2018).…”
Section: Introductionmentioning
confidence: 99%